Clinical and Radiographic Outcomes of Revision Total Ankle Arthroplasty Using the INBONE II Prosthesis. (7th September 2022) - Jamjoom, Bakur A.; Siddiqui, Bobby M.; Salem, Hatem; Raglan, Martin; Dhar, Sunil
Abstract : Background: The literature on the outcome of revision total ankle arthroplasty (TAA) remains limited. In this study, we aimed to report the clinical and radiographic outcomes of revision TAA at a high-volume center in the United Kingdom. Methods: This study was a retrospective review of 28 patients who underwent 29 revision TAAs using the INBONE II Total Ankle System (Wright Medical Technology/Stryker). Demographic, radiographic, and patient-reported outcome measure data were analyzed. Results: The mean duration from primary TAA to revision was 87.5 months (range, 16 to 223 months). The main indication for the revision was aseptic loosening after the primary TAA (83%). Additional procedures were required in 76% of ankles. At a mean follow-up of 40 months (range, 24 to 60 months), the infection rate was 7%, the reoperation rate was 7%, and the implant survival rate was 97%. A significant postoperative improvement in the radiographic component alignment measures was observed. The subsidence, loosening, and heterotopic ossification rates in this study were comparable with those in other reports and did not influence the clinical outcome. A significant improvement was observed in the Manchester-Oxford Foot Questionnaire (MOXFQ) in all domains and the EuroQol-5 Dimensions (EQ-5D) in 3 domains at 24 months postoperatively. Conclusions: Revision TAA using the INBONE II prosthesis was associated with good short-term survival and improvement in postoperative scores at 2 years. Maintenance of the postoperatively improved alignment was documented at the follow-up. The results of this study support the notion that revision TAA is a satisfactory option for failed primary TAA. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.